Pengembangan Sistem Informasi Surveilans Tb Berbasis Komputer Untuk Mendukung Evaluasi Hasil Kegiatan Program Penanggulangan TB (P2TB) - Sugiarsi, Sri (Speed - Sentra Penelitian Engineering dan Edukasi, 2012)
Abstract: Activities of TB surveillance at Sukoharjo District Health Office only resulted three indicators of P2TB although the sources of the TB data had been available completely. This condition caused the problems for HeadÂ  of the Distric Health Office to know coverage of services, to extend coverage of program, and to know the result of treatment. Therefore, It needs the information system that could overcome the problems. The aim of research is the develop information system of TB surveillance to support the evaluating of P2TB. This was an applied research using a qualitative method and applying the plan of system by steps of FAST (Framework for the Application of System Techniques). Research design was Pre-Experimental using The Group Pretest-Posttest. The Subjects were Head of the District helth Office, Head of Sub department of Prevention and Eradication. The Objects were the procedure and the structure of information system of TB surveillance. Data analysis divided into two methods as follows: Content Analysis was used for in-depth interview data and Descriptive Analysis was used for evaluating the old and the new system. The result of the research shows that information system development of TB surveillance has to be done based on the aspects of a technique, an operation, a schedule, and an economic. The problems in the old system were simplicity, accurateness, and representative. Those problems were caused by input on the system (redundancy data, and file saved separately), process (indicator had not been calculated by Management System of data Basis ), and output (displayed in table, the reports did not adjust a necessity on the management level). The new system couldÂ  overcome the old systemâs problems and weaknesses. It could be used to support the evaluation of P2TB. The total considered average in the old system was 2,29 and the total considered average in the new system is 4,27. The new system could result seven indicators of P2TB, which could be used for a basic of evaluating of program. Therefore, head of the District health Office could make a policy with using the new system. The weaknesses of the new system are as follows: It could not be used for the Health center level, and could not result information about monitoring of drinking a mediine. Key Words : Information System,TB Surveillance